In vivo imaging of click-crosslinked hydrogel depots following intratympanic injection - Ju, Hyeon Jin; Park, Mina; Park, Ji Hoon; Shin, Gi Ru; Choi, Hak Soo; Suh, Myung Whan; Kim, Moon Suk (Materials, 2020)
In this study, we developed injectable intratympanic hyaluronic acid (HA) depots for the treatment of hearing loss. We prepared an injectable click-crosslinking formulation by modifying HA with tetrazine (HA-TET) and trans-cyclooctene (HA-TCO), which crosslinked to form an HA depot (Cx-HA). Preparation of the click-crosslinkingHAformulation was facile, and Cx-HA depot formation was reproducible. Additionally, the Cx-HA hydrogel was significantly stiffer than HA hydrogel. To monitor the degradation pattern of hydrogels, we mixed a zwitterionic near-infrared (NIR) fluorophore (e.g., ZW800-1C) in the click-crosslinking HA formulation. Then, HA-TET and HA-TCO solutions containing ZW800-1C were loaded separately into the compartments of a dual-barrel syringe for intratympanic injection. The Cx-HA depots formed quickly, and an extended residence time in the tympanic cavity was confirmed by performing NIR fluorescence imaging. We have successfully prepared an injectable click-crosslinking HA formulation that has promise as an intratympanic drug depot.
Keywords: Cross-linked hydrogels; Degradation patterns; In-Vivo imaging; Intratympanic; Near infra red; Nir fluorescence imaging; Residence time; Tympanic cavity; Click-crosslinking; Depot; Hyaluronic acid; Intratympanic injection; Near-infrared fluorescence